Pengembangan Bahan Ajar Fisika Berbasis I-SETS Terkomplementasi Karakter Pada Materi Hukum Gravitasi Newton (UPEJ Unnes Physics Education Journal, 2019)
Teaching materials used in schools are still limited to the presentation of concise material and short formulas so that students feel difficulties when solving problems related to life. Teaching materials based on I-SETS complemented characters presented in material related to aspects of Islam, science, environment, technology, and society as well as character values so students motivated to be more active, creative, and think critically in solving problems. The purposes of this research are determine the characteristics, feasibility, readability, and practicality of gravity teaching materials. The method used is Research and Development. The teaching materials produced have several characteristics based on 3 aspects, namely content, presentation, and language. The result of the feasibility test indicates that teaching material is suitable to used in learning with a percentage of 87.50%. The result of readability test indicates that teaching material is easily understood by students with a percentage of 86.66%. The result of operational field test show that teaching material is practical to used in learning with a percentage of 85.91%.